Embryo and fetal pathology color atlas with ultrasound correlation - Gilbert-Barness, Enid 1927- (Cambridge University Press, 2004)
Exhaustively illustrated in color with over 1000 photographs, figures, histopathology slides, and sonographs, this uniquely authoritative atlas provides the clinician with a visual guide to diagnosing congenital anomalies, both common and rare, in every organ system in the human fetus. It covers the full range of embryo and fetal pathology, from point of death, autopsy and ultrasound, through specific syndromes, intrauterine problems, organ and system defects to multiple births and conjoined twins. Gross pathologic findings are correlated with sonographic features in order that the reader may confirm visually the diagnosis of congenital abnormalities for all organ systems. Obstetricians, perinatologists, neonatologists, geneticists, anatomic pathologists, and all practitioners of maternal-fetal medicine will find this atlas an invaluable resource.